Seasat views oceans and sea ice with synthetic-aperture radar - Fu, Lee-Leung; Holt, Benjamin; United States. National Aeronautics and Space Administration; Jet Propulsion Laboratory (U.S.) (Pasadena : California Institute of Technology, Jet Propulsion Laboratory, 1982)
Mode of access: Internet.